Gambaran Pengetahuan Masyarakat Tentang Swamedikasi Antidiare Di Pelabuhan Mamuju (Kasiwa) - Zalsabila Riska; Wita Oileri Tikirik (CV. SINAR HOWUHOWU, 2026)
This study aims to determine the level of community knowledge regarding self-medication for diarrhea at Mamuju Port (Kasiwa). This research employed a quantitative descriptive design using a purposive sampling technique. The sample consisted of 80 respondents from the Kasiwa Port area. Data were collected using a questionnaire covering knowledge about the definition, usage, and proper administration of antidiarrheal drugs. Data analysis was conducted using univariate analysis and presented in frequency and percentage distributions. The results showed that most respondents were female (57.5%) and had a senior high school education background (53.75%). The level of knowledge regarding antidiarrheal self-medication was predominantly categorized as low (60%), followed by good (32%) and moderate (8%). These findings indicate that community understanding of appropriate and rational use of antidiarrheal medication remains inadequate. Therefore, active involvement of healthcare professionals in providing education and counseling is needed to improve community knowledge and promote safe and responsible self-medication practices.